Manajemen Strategi Kepemimpinan Kepala Sekolah Pada Projek Penguatan Profil Pelajar Pancasila di SD Negeri 70 Ambon - Nurlaila Latuliu; Rudolf Kempa; Sumarni Rumfot (Jurnal Pendidikan Geografi Unpatti, 2025)
This study aims to analyze the school principal's strategic management in implementing the Project to Strengthen the Pancasila Student Profile (P5) at SDN 70 Ambon. The research used a qualitative approach with a case study method. Data were collected through interviews, observations, and documentation, and analyzed interactively based on the Miles and Huberman model. The findings indicate that the principal applies a collaborative leadership style that is responsive to both internal and external school needs. The strategies implemented include SWOT-based planning, optimal resource allocation, participatory evaluation, and corrective actions focused on continuous improvement. Additionally, teacher motivation and parental involvement play a crucial role in supporting the success of the project. The impact of P5 implementation is reflected in the improved character development of students aligned with Pancasila values and the enhanced public image and competitiveness of the school. This research concludes that effective management strategies in P5 implementation not only strengthen the school culture but also establish a sustainable and adaptive education system in response to contemporary challenges